1985
DOI: 10.1515/cclm.1985.23.7.377
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic B-Cell Peptides as Parameters for Diagnosis and Localisation of Hormone Secreting Tumours

Abstract: Summary: Insulin, C-peptide and proinsulin were measured in peripheral blood of 11 patients suffering from different types of hormone-producing pancreatic B-cell tumours. While proinsulin was elevated in 10/11 patients during prolonged fasting, C-peptide and insulin levels were found within the reference ränge in 5/ 11 and 3/5 cases respectively. A rapid insulin assay performed during surgery was helpful for localisation and identification of the respective tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Service et al reported that insulinoma patients had C-peptide values at the end of the 72 h fasts greater than or equal to 0.20 nmol/mL (0.60 ng/mL); however, our case does not fulfill that criterion even before conducting the prolonged fasting test [12]. According to the data from the literature, the molar ratio of serum C-peptide to insulin is, in general, decreased in patients with insulinoma than normal subjects, while in our case the ratios were much lower (Table 2) [18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Service et al reported that insulinoma patients had C-peptide values at the end of the 72 h fasts greater than or equal to 0.20 nmol/mL (0.60 ng/mL); however, our case does not fulfill that criterion even before conducting the prolonged fasting test [12]. According to the data from the literature, the molar ratio of serum C-peptide to insulin is, in general, decreased in patients with insulinoma than normal subjects, while in our case the ratios were much lower (Table 2) [18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 52%
“…In conclusion, this case report emphasizes some unusual features of an insulinoma, including a positive [18] 14.7 8 Kajinuma et al [19] 12.1 20 Okada et al [20] 11.2 136 Our case (after surgery) 17.6 1 Insulinoma Smythe et al [21] 20.0 1 Katabami et al [22] 7.2 4 Gin et al [23] 6.3 8 Sakai et al [18] 6.1 1 Scarlett et al [24] 5.9 1 Saudek [25] 5.6 1 Gerbitz and Spelsberg [26] 5.0 5 Lebowitz and Blumenthal [27] 4.9 3 Kondo et al [28] 4.2 3 Service [29] 3.6 1 Ciavarella et al [30] 2.9 1 Turner and Heding [31] 2.0 2 Our case (before surgery) 2.0 1 insulin response to secretin and decreased C-peptide levels, of which clinicians should be aware. The diagnosis of insulinoma should not depend on some particular endocrinological tests and should be made comprehensively.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore nesidioblastosis tissue seems to be the ideal source for preparation of human islets. The proliferative power of the isolated nesidioblastosis islets remained demonstrable in cell culture up to several months (10). The tissues (normal pancreas and nesidioblastosis 2) used in this study for immunofluorescence were from two donors with blood group 0, thus there was no interference with the blood group system.…”
Section: Discussionmentioning
confidence: 94%